HUBUNGAN ANTARA PRODUKTIVITAS DAN KREATIVITAS GURU DALAM MENGAJAR DENGAN MINAT BELAJAR PESERTA DIDIK PADA MASA PANDEMI COVID-19 DI SMK - Betaria Sitanggang; Muhammad Amin (Universitas Negeri Medan, 2022)
AbstractThis study aims to determine: (1) the relationship between teacher productivity in teaching and students' interest in learning during the covid-19 pandemic; (2) the relationship between teacher creativity in teaching and students' interest in learning during the covid-19 pandemic; (3) the relationship between teacher productivity and creativity in teaching and students' interest in learning during the covid-19 pandemic. The research method used is ex post facto. The population in this study amounted to 75 respondents with a sample of 63 respondents who were taken through the Purposesive Sampling technique. Prerequisite tests used in this study include normality test, linearity test, multiple regression coefficient test. Hypothesis testing includes partial test (t test), simultaneous test (F test), hypothesis test 1, hypothesis test 2 and hypothesis test 3. Data collection is done by means of observation and distributing questionnaires. The research questionnaire was first tested for validity and reliability. Then the data collected was processed with the help of Ms. Excel and SPSS version 22 software. The results of this study prove that: (1) There is a relationship between teacher productivity in teaching and students' interest in learning with the results of the research that the correlation coefficient of 0.595 is greater at the significance level of 0.05 or 5%. (2) There is a relationship between teacher creativity in teaching and students' interest in learning with the results of the research the correlation coefficient of 0.593 is greater at the significance level of 0.05 or 5%. (3) There is a relationship between teacher productivity and creativity in teaching and students' interest in learning with the results of the F test calculation, the Fcount value is 22.850 and Ftable is 2.76. Thus the Fcount > Ftable (22.850 > 2.76) and the significance value (0.000 < 0.05).Key Words: Teacher Productivity, Teacher Creativity, Students' Interest in Learning. AbstrakPenelitian ini bertujua untuk mengetahui: (1) hubungan produktivitas guru dalam mengajar dengan minat belajar peserta didik pada masa pandemi covid-19; (2) hubungan kreativitas guru dalam mengajar dengan minat belajar peserta didik pada masa pandemi covid-19; (3) hubungan produktivitas dan kreativitas guru dalam mengajar dengan minat belajar peserta didik pada masa pandemi covid-19. Metode penelitian yang digunakan yaitu ex post facto. Populasi dalam penelitian ini berjumlah 75 responden dengan sampel sebanyak 63 responden yang diambil melalui teknik Purposesive Sampling. Uji prasyarat yang digunakan dalam penelitian ini meliputi uji normaltas, uji lineritas, uji koefisien regresi ganda. Uji hipotesis meliputi uji parsial (uji t), uji simultan (uji F), uji hipotesis 1, uji hipotesis 2 dan uji hipotesis 3. Pengumpulan data dilakukan dengan cara observasi dan penyebaran angket. Angket penelitian terlebih dahulu diuji validitas dan reliabilitas. Kemudian data yang terkumpul diolah dengan bantuan Ms. Excel dan software SPSS versi 22. Hasil penelitian ini membuktikan bahwa: (1) Adanya Hubungan antara produktivitas guru dalam mengajar dengan minat belajar peserta didik dengan hasil penelitian koefisien korelasi sebesar 0,595 lebih besar pada taraf signifikansi sebesar 0,05 atau 5%. (2) Adanya Hubungan antara kreativitas guru dalam mengajar terhadap minat belajar peserta didik dengan hasil penelitian koefisien korelasi sebesar 0,593 lebih besar pada taraf signifikansi sebesar 0,05 atau 5%. (3) Adanya Hubungan antara produktivitas dan kreativitas guru dalam mengajar dengan minat belajar peserta didik dengan hasil perhitungan uji F diperoleh nilai Fhitung sebesar 22,850 dan Ftabel sebesar 2,76. Dengan demikian nilai Fhitung > Ftabel (22,850 > 2,76) dan nilai signifikasi (0,000 < 0,05)..Kata Kunci: Produktivitas Guru, Kreativitas Guru, Minat Belajar Peserta Didik